The Macroeconomic Effects of Fiscal Consolidation in Emerging Economies : Evidence from Latin America - Carriere-Swallow, Yan (IMF Working Papers; Working Paper ;, 2018)
We estimate the short-term effects of fiscal consolidation on economic activity in 14 countries in Latin America and the Caribbean. We examine contemporaneous policy documents to identify changes in fiscal policy motivated by a desire to reduce the budget deficit and not by responding to prospective economic conditions. Based on this narrative dataset, our estimates suggest that fiscal consolidation has contractionary effects on GDP, consistent with a multiplier of 0.9. We find these effects to be close to those in OECD countries based on a similarly constructed dataset (Devries and others, 2011). We also find similar estimation results for the two groups of economies for the effect of fiscal consolidation on the external current account balance, providing support for the twin deficits hypothesis.